Serine and threonine residues of the cytoplasmic tail of D1-like dopaminergic receptors differentially modulate their pharmacological and regulatory properties - Laquerre, Vincent (University of Ottawa (Canada), 2010)
The molecular basis for distinct pharmacological and regulation properties of human D1-like dopaminergic receptors (D1R and D5R) remains elusive. To address this issue, the contribution of all serine (Ser) and threonine (Thr) of cytoplasmic tail (CT) of D1R and D5R was investigated using phosphodeficient (PDT) mutants. Results obtained using radioligand and whole cell cAMP assays indicate that Ser/Thr residues regulate in a subtype-specific manner the properties of D1R and D5R. PDT-D5R exhibited an increase in agonist binding affinity, constitutive activity and DA-mediated maximal stimulation. Meanwhile, only PDT-D1R exhibited a decrease in short-term desensitization compared to wild type receptor. In contrast, both mutants were resistant to agonist-induced down-regulation. Overall, the targeting Ser/Thr residues of CT may prove useful in the development of new dopaminergic drugs not acting at the transmembrane ligand binding pocket and thus potentially provide alternative therapeutic approaches for pathological conditions associated with compromised D1-like function such as Parkinson's.
Keywords: Biology, Neuroscience.